2018
DOI: 10.1039/c8rp00074c
|View full text |Cite
|
Sign up to set email alerts
|

Student-centred active learning approaches to teaching quantum chemistry and spectroscopy: quantitative results from a two-year action research study

Abstract: In this article, I propose a student-centred approach to teaching quantum chemistry and spectroscopy at the bachelor-level that extends active learning principles outside course lectures. The aim is to elucidate what type of methodology is most appropriate and efficient for this context and student population, and how this incorporation of active learning elements impacts learning. Three quantitative learning indicators are used to measure the effectiveness of the proposed approach, including exercise points o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 109 publications
1
20
0
Order By: Relevance
“…Other significant correlations indicated that the tasks also seemed meaningful and relevant to their learning. This could help explain a previous finding that despite the substantial learning gains observed between 2016 and 2017, a significant minority of students showed virtually no improvement in their conceptual test score between pre-and post-course tests (Partanen, 2018). The current results suggest that there might be a portion of students who remain on the fringes of the course, disengaged and not actively participating in the various group activities.…”
Section: Lecture Videos (2016-2017)supporting
confidence: 55%
See 4 more Smart Citations
“…Other significant correlations indicated that the tasks also seemed meaningful and relevant to their learning. This could help explain a previous finding that despite the substantial learning gains observed between 2016 and 2017, a significant minority of students showed virtually no improvement in their conceptual test score between pre-and post-course tests (Partanen, 2018). The current results suggest that there might be a portion of students who remain on the fringes of the course, disengaged and not actively participating in the various group activities.…”
Section: Lecture Videos (2016-2017)supporting
confidence: 55%
“…The quantitative analysis presented in my previous publication (Partanen, 2018) and the complementary analysis of student experiences presented here demonstrate that the incorporation of active learning principles outside course lectures improves both student learning and motivation. These findings reveal the benefits of adopting a multifaceted and integrated approach to both exercises and lecturing in challenging subjects like quantum chemistry and thermodynamics, where quantitative and qualitative understanding are equally important.…”
Section: Conclusion and Implications For Teachingmentioning
confidence: 55%
See 3 more Smart Citations